An analysis of malaysian public policy in disaster risk reduction: An endeavour of mitigating the impacts of flood in Malaysia - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon Yew; Noor Amira Syazwani, Abd Rahman (Human Resource Management Academic Research Society (HRMARS), 2022)
In light of climate change and sustainable development issues, holistic flood risk reduction strategies must be integrated into policy initiatives to reduce flood threats. Numerous countries have been devastated by recent floods, which have claimed many lives and wrecked the economy in the affected areas. In most nations, there are public policies in place to mitigate the impact of flooding on citizens. Policies adopted are mostly based on international frameworks, including the Yokohama Strategy, the Hyogo Framework for Action 2005-2015, and the Sendai Framework for Disaster Risk Reduction. With the help of international frameworks, Malaysia has also developed several disaster guidelines and public policies. Some people died as a result of their failure to escape from the floodwaters, but many more were injured. Since Malaysia is plagued by floods, this study aims to examine the effectiveness of Malaysian public policy related to flood management. This qualitative research examines and evaluates publications from a variety of sources, especially published journal articles. The findings revealed that Malaysia lacks an effective legislative framework to integrate policies and mechanisms for flood management. Directive No. 20 of the National Security Council provides precise standards, but it must also rely on a range of regulations not specifically adopted for flood control. Besides that, the Directive is formulated to cater to general disasters and is not specifically focused on the flood. The Directive also did not highlight the need to engage citizens in flood management. Besides that, some local plans are less concerned with the criteria that help to inculcate preparedness in the face of flood risk. Policymakers in Malaysia should be able to use the findings of this research to craft a public policy that specifically addresses the country's flood concerns. Scholars are encouraged to conduct an additional study to obtain a better understanding of public policy issues in Malaysia, particularly floods.